(untitled) (Research, Society and Development, 2025)
Objective: To synthesize scientific evidence on pressure injury prevention in terminally ill cancer patients, highlighting risk factors, nursing interventions, and care strategies. Method: An integrative review was conducted in the PubMed, SciELO, LILACS, and Google Scholar databases between August and September 2025, using the DeCS/MeSH descriptors. Articles published between 2014 and 2024, in Portuguese, English, and Spanish, were included. Results: 120 articles were initially identified; after the selection process, 32 studies comprised the final sample. The main risk factors described were immobility, cachexia, and metabolic alterations. The most frequent interventions were repositioning, use of support surfaces, maintenance of skin integrity, and education of family members/caregivers. The Braden Scale was the most frequently used instrument. Conclusion: Nursing plays a central role in preventing pressure injuries in cancer patients undergoing palliative care, requiring institutional protocols and ongoing staff training.